2008
DOI: 10.1258/acb.2007.007156
|View full text |Cite
|
Sign up to set email alerts
|

Association of leprosy with HLA-DRB1 in an Argentinean population

Abstract: Background: Previous studies have suggested an influence of HLA molecules on the regulation of the anti Mycobacterium leprae immune response. Methods: DNA typing of HLA-DRB1 alleles in 71 leprosy patients and 81 healthy controls was performed. Genomic DNA was extracted from peripheral blood and used as a template to amplify the polymorphic second exon of the HLA-DRBl by the ploymerase chain reaction (PCR). PCR products were hybridized separately with sequence-specific oligonucleotides. Results: DRB1Ã 1401 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Studies of associations between HLA type and recognition of ESAT-6 among tuberculosis patients have noted that individual epitopes can be presented by diverse HLA types to human T cells, as well as that a given HLA type can present distinct epitopes [21, 22]. Our findings support earlier evidence of humoral responses to mycobacterial antigens [12, 23], and with the published literature regarding HLA specificity for mycobacterial antigens in tuberculosis and leprosy—two kindred granulomatous disorders [2427]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies of associations between HLA type and recognition of ESAT-6 among tuberculosis patients have noted that individual epitopes can be presented by diverse HLA types to human T cells, as well as that a given HLA type can present distinct epitopes [21, 22]. Our findings support earlier evidence of humoral responses to mycobacterial antigens [12, 23], and with the published literature regarding HLA specificity for mycobacterial antigens in tuberculosis and leprosy—two kindred granulomatous disorders [2427]. …”
Section: Discussionsupporting
confidence: 89%
“…Studies of HLA associations with tuberculosis and lepromatous antigens reveal that most antigens are recognized in association with HLA-DR molecules (serologically defined as HLA-DR1 to HLA-DR10) [2427]. HLA molecules encoded by HLA-DRB3 (HLA-DR52) and HLA-DRB4 (HLA-DR53) are also noted to be important in presentation of antigens from Mycobacterium tuberculosis and Mycobacterium leprae to Th-1 cells [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Risk for leprosy associated with the DRB1 * 10 allele has been described in Turkish, Vietnamese, and Brazilian populations [17, 36], whereas the HLA-DRB1 * 14 allele was associated with the TT group in a population from north-eastern Brazil [42] and DRB1 * 14:01 and DRB1 * 14:06 were associated with leprosy per se in Argentinean population [37]. A protective effect on leprosy has been described for DRB1 * 04 in Brazilian, Korean, Japanese, Vietnamese, Argentinean, and Taiwanese populations [13, 30, 34, 36, 40].…”
Section: Classical Hla Class II Genesmentioning
confidence: 99%
“…Table 1 summarizes both positive (association found) and negative (no association detected) association studies of leprosy for non-HLA candidate genes. A series of linkage and candidate gene studies has demonstrated associations of the major histocompatibility complex (MHC) class I and II loci (especially with HLA-DR2 alleles) with leprosy susceptibility (30,39,277,305,316,317,331,347). Those and other studies of the MHC region were extensively reviewed elsewhere previously (108,315) and will not be included in this review.…”
Section: Study Design For Complex Diseasesmentioning
confidence: 99%
“…While some studies support an association of the SNP GϪ308A with altered susceptibility to leprosy overall or leprosy type, the SNP appears to have opposite effects on leprosy polarity (tuberculoid versus lepromatous) in different populations. The TNF gene is located on chromosome 6q23-12 in a region in close linkage with HLA-DR (51, 187, 213 locus that has also been associated with leprosy (39,40,108,315,317). Similarly, the TNF Ϫ308 SNP is in LD with the LTA gene, and a haplotype containing the Ϫ308A allele and LTA SNPs ϩ10A, ϩ252G, and ϩ723A has been shown to be associated with increased LTA transcriptional activity (159).…”
Section: Cytokinesmentioning
confidence: 99%